2020
DOI: 10.1007/s10653-020-00685-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater safety surrounding contaminated water storage sites using multivariate statistical analysis and Heckman selection model: a case study of Kazakhstan

Abstract: Petrochemical enterprises in Kazakhstan discharge polluted wastewater into special recipients. Contaminants infiltrate through the soil into the groundwater, which potentially affects public health and environment safety. This paper presents the evaluation of a 7-year monitoring program from one of the factories and includes nineteen variables from nine wells during 2013-2019. Several multivariate statistical techniques were used to analyse the data: Pearson's correlation matrix, principal component analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…Previous research has shown that hydrocarbons, originating from the petrochemical industry, are practically ubiquitous in groundwater, are usually only biodegraded to a limited extent, and the resulting contaminant plumes may be several kilometers long (Balderacchi et al 2013). Measured concentrations in groundwater samples show that the amount of TPH constantly exceeds the permissible limit in all monitoring wells surrounding Sarymsaq, which confirms the presence of groundwater pollution in the area (Radelyuk et al 2021b). The amount of TPH usually has maximum peaks during the spring season, which can be explained by intensive snowmelt and large infiltration of water through the soil profile.…”
Section: Study Area Descriptionmentioning
confidence: 53%
See 3 more Smart Citations
“…Previous research has shown that hydrocarbons, originating from the petrochemical industry, are practically ubiquitous in groundwater, are usually only biodegraded to a limited extent, and the resulting contaminant plumes may be several kilometers long (Balderacchi et al 2013). Measured concentrations in groundwater samples show that the amount of TPH constantly exceeds the permissible limit in all monitoring wells surrounding Sarymsaq, which confirms the presence of groundwater pollution in the area (Radelyuk et al 2021b). The amount of TPH usually has maximum peaks during the spring season, which can be explained by intensive snowmelt and large infiltration of water through the soil profile.…”
Section: Study Area Descriptionmentioning
confidence: 53%
“…As residents of the rural area near the industrial zone are using the groundwater from the shallow aquifer for their drinking and domestic purposes (Tussupova et al 2016), an investigation was needed to assess potentially affected sites and to prevent members of the local community from drinking unsafe water. The source of potential contamination in this case study is a recipient pond "Sarymsaq" (Appendix A), where wastewater is discharged by the cluster of local petrochemical industry sites (Radelyuk et al 2021b).…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karunanidhi et al (2020a, b) described subsurface hydrogeochemical processes in a geologically heterogeneous semi-arid region of south India using mass transfer and fuzzy comprehensive modelling, and reported high influence of silicate weathering, ion exchange and gypsum dissolution on overall quality of the groundwater. Similarly, Radelyuk et al (2020) assessed groundwater safety close to contaminated water storage sites in Kazakhstan using multivariate statistical analysis and Heckman selection model (a very first attempt to evaluate environmental factors) and confirmed a high loading of anthropogenic contamination from the petrochemical industry coupled with natural geochemical processes.…”
Section: Groundwater Modellingmentioning
confidence: 83%